Severe pneumonia caused by Chlamydia psittaci: report of two cases and literature review - Nini Dai; Qiuyu Li; Jiayi Geng; Wei Guo; Wei Yan (Journal of Infection in Developing Countries, 2022)
Introduction: Chlamydia psittaci pneumonia is a zoonotic infectious disease caused by Chlamydia psittaci. Its clinical manifestations are nonspecific. Diagnosis of the disease is difficult. In recent years, next-generation sequencing has played an important role in pathogen detection. We report two cases with severe Chlamydia psittaci pneumonia confirmed by next-generation sequencing.